The Precise Diagnosis of Wolfram Syndrome Type 1 Based on Next-Generation Sequencing - Wang, Dan-Dan; Hu, Fang-Yuan; Gao, Feng-Juan; Zhang, Sheng-Hai; Xu, Ping; Tian, Guo-Hong; Wu, Ji-Hong (Frontiers in Genetics, 2019)
Purpose: To explore a method for the early, rapid and accurate diagnosis of Wolfram syndrome 1 (WS1) and further enrich the spectrum of WFS1 mutations in the Chinese population. Methods: We analyzed 279 patients with unexplained optic atrophy using next-generation sequencing (NGS). All patients underwent detailed clinical evaluations. Furthermore, Sanger sequencing and cosegregation analyses were performed within families. Results: Five patients with WS1 were identified in four unrelated families, and their clinical features were reviewed in detail. Seven variants of WFS1 were detected, including three reported variants (p.G674R, p.Tyr508Cysfs*34 and p.G702D) and four novel variants (p.W540G, p.K634*, p.F770C and p.Q584P). Furthermore, the variant p.G674R was recurrent. Conclusion: Considering that WS1 is a rare progressive neurodegenerative disease, early diagnosis is beneficial to the systematic evaluation, monitoring and management of complications to improve patient quality of life and delay the progression of the disease. In the future, precise diagnosis on the basis of clinical manifestation and genetic testing will become the gold standard for the diagnosis of hereditary eye diseases and syndromes. Finally, our results further increase the spectrum of WFS1 mutations by adding four novel variants to the limited data available in the Chinese population.